Infographics as a Tool to Improve Pregnancy Vaccination Leaflets - Jeanne Muizelaar; Mark Bos (University of Zurich, IKMZ - Department of Communication and Media Research, 2024)
Printed leaflets continue to be an important information source in health contexts. Visuals can increase engagement with a leaflet, facilitate understanding, and minimise cognitive load. In this study, two information leaflets, one with and one without infographics, were investigated. The leaflets aimed to inform pregnant people about vaccination against influenza and pertussis. Through a questionnaire, the effects of infographics on the opinion on the leaflet, health beliefs, and vaccination intent were investigated. One hundred and seventy-seven Dutch-speaking pregnant people took part in the study. The visually enhanced leaflet was shown to be better appreciated, reflected by better ratings and higher levels of engagement compared to the textual version. The visually enhanced leaflet also significantly increased vaccination intent for pertussis, but not for influenza. The findings of this study provide insights into how visuals can contribute to effective health communication.